Quality of Life in Outpatient Primary Hypothyroidism in Riyadh - Naif Alrudian, P.J.Parameaswari, Rayan Alqahtani, Rajab Ali Khawaja, Saleh Emad Abu-Alreesh, Yaser Saleh Alkraidis, Abdulaziz Ibrahim Alhonaizil, Deepak Pathania (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To estimate the Primary Hypothyroidism and to study its effects on the Quality of Life of those patients. Study design: It was a Cross-Sectional Study done using random sampling. Sample size: 463 patients Duration and location of the study: It was done between December 2018 and December 2019 in outpatient clinics of a tertiary care hospital in Riyadh. Study tool: The quality of life of these patients was assessed by World Health Organization (WHO) Health Survey 36-Item Short Form (SF-36) questionnaire with a score less than 50% was considered to be ‘Poor quality’. Results: The response rate of participants was 92.6% and the prevalence of Primary Hypothyroidism was observed to be 47.8%. They experienced a poor mental health with an average score (35.1 ± 1.6). Factors such as illiteracy (35.0 ±1.0), primary level of education (29.4 ± 3.6), housewife (43.49 ± 38.19) and the retired patients (20.31 ± 37.88) had a poor Physical function (P=0.001). However, the patients without primary hypothyroidism had better quality of life with physical, social and mental functional scores (P=0.001). The statistically significant poor quality of life observed due to poor education, income level and marital status exposed the need for the guidelines and management of this morbidity in the Saudi community. Keywords: Primary Hypothyroidism, SF-36, Quality of Life, Cross-Sectional study